Squaring the cycle: Financial cycles, capital flows and macroprudential policy in the Euro area - Silvia Merler (Bruegel, 2015)
Before the financial and economic crisis, monetary policy unification and interest rate convergence resulted in the divergence of euroarea countries' financial cycles. This divergence is deeply rooted in the financial integration spurred by currency union and strongly correlated with intra-euro area capital flows. Macro-prudential policy will need to deal with potentially divergent financial cycles, while catering for potential cross-border spillovers from domestic policies, which domestic authorities have little incentive to internalise. The current framework is unfit to deal effectively with these challenges. The European Central Bank should be responsible for consistent and coherent application of macro-prudential policy, with appropriate divergences catering for national differences in financial conditions. The close link between domestic financial cycles and intra-euro area capital flows raises the question of whether macro-prudential policy in the euro area can be compatible with free flows of capital. Financial cycle divergence had its counterpart in the build-up of macroeconomic imbalances, so effective implementation of the Macroeconomic Imbalance Procedure would support and strengthen macro-prudential policy.
Keywords: 330